The Influence of Café Atmosphere, Service Quality, and Product Variety on Purchase Decisions at Ngopidiaphen in Pontianak City - Detia Meisya; Helman Fachri (SAINTIS Publishing, 2025)
This study aims to analyze the influence of Café Atmosphere, Service Quality, and Product Variety on Purchase Decisions at Ngopidiaphen in Pontianak City. This research employs a quantitative approach with a total of 100 respondents selected using an accidental sampling technique. Data were collected through observation, interviews, and questionnaires. The results of multiple linear regression analysis show the equation Y = 1.110 + 0.274X₁ + 0.182X₂ + 0.202X₃, with a correlation coefficient (R) of 0.719 indicating a strong relationship, and a coefficient of determination (R²) of 51.7%, meaning the remaining variation is influenced by other factors outside this study. The F-test results show that Café Atmosphere, Service Quality, and Product Variety simultaneously have a positive and significant effect on Purchase Decisions, with an F calculated value of 34.237 F table 3.09 and a significance value of 0.000 0.05. Partial t-tests also show that each variable has a positive and significant effect, with t calculated values for Café Atmosphere (3.133), Service Quality (2.077), and Product Variety (2.561), all greater than the t table value of 1.660. In conclusion, a comfortable café atmosphere, high-quality service, and diverse products make a real contribution to increasing consumers’ purchase decisions at Ngopidiaphen. The practical implication is that café owners are advised to consistently maintain the atmosphere, improve service quality, and innovate their menu. Future research is expected to include other variables such as promotion or pricing to produce more comprehensive results.